Resonance‐Activated Spin‐Flipping for Efficient Organic Ultralong Room‐Temperature Phosphorescence. Issue 44 (10th September 2018) - Tao, Ye; Chen, Runfeng; Li, Huanhuan; Yuan, Jie; Wan, Yifang; Jiang, He; Chen, Cailin; Si, Yubing; Zheng, Chao; Yang, Baocheng; Xing, Guichuan; Huang, Wei
Abstract: Triplet‐excited‐state‐involved photonic and electronic properties have attracted tremendous attention for next‐generation technologies. To populate triplet states, facile intersystem crossing (ISC) for efficient exciton spin‐flipping is crucial, but it remains challenging in organic molecules free of heavy atoms. Here, a new strategy is proposed to enhance the ISC of purely organic optoelectronic molecules using heteroatom‐mediated resonance structures capable of promoting spin‐flipping at large singlet–triplet splitting energies with the aid of the fluctuation of the state energy and n‐orbital component upon self‐adaptive resonance variation. Combined experimental and theoretical investigations confirm the key contributions of the resonance variation to the profoundly promoted spin‐flipping with ISC rate up to ≈10 7 s −1 in the rationally designed NPX (X = O or S) resonance molecules. Importantly, efficient organic ultralong room‐temperature phosphorescence (OURTP) with simultaneously elongated lifetime and improved efficiency results overcoming the intrinsic competition between the OURTP lifetime and efficiency. With the spectacular resonance‐activated OURTP molecules, time‐resolved and color‐coded quick response code devices with multiple information encryptions are realized, demonstrating the fundamental significance of this approach in boosting ISC dynamically for advanced optoelectronic applications. Abstract : Dynamically promoted spin‐flipping in purely organic molecules is realized through the fluctuation of excited‐state energies and n‐orbital components upon heteroatom‐mediated resonance variation for enhanced intersystem crossing (ISC). The rationally designed resonance molecules exhibit high ISC rate and excellent organic ultralong room‐temperature phosphorescence (OURTP) with simultaneously elongated lifetime and improved efficiency, overcoming the intrinsic competition between OURTP lifetime and efficiency.